STRATEGIC LAND USE MANAGEMENT: ENVIRONMENTAL TRADE-OFFS FOR THE PURPOSE OF ENSURING THE SUSTAINABILITY OF AGRICULTURAL ENTERPRISES - Dubovitski, Alexander A.; Klimentova, Elvira A.; Averina, Olga I.; Galitskaya, Yulia N.; Tsykora, Aleksander A. (Economics of Agriculture, 2022)
An important condition for the formation of sustainability of agriculture is the ability to achieve environmental trade oﬀs in the process of land use. The purpose of research is development of methodical approaches to formation of strategy of rational land use by means of improvement of administrative activity at microlevel. Authors have formulated concept of strategy of rational use of land, basic principles, elements and sequence of its construction. The structural mechanism of realization of strategy of maintenance of readiness of the personnel to rational use of land, and also bringing material and technical, financial and land resources in strategic conformity for achievement of ecological compromises in the course of conducting agricultural activity is oﬀered. The authors developed a conceptual model of a strategic map of rational land use on the basis of a balanced system of economic and environmental indicators, and proposed directions for its implementation.